Physical Stability Evaluation of Topical Formulation Containing Turmeric (Curcuma longa L.) Leaf Extract as a Potential Natural Repellent - Ulya, Tuhfatul; Ratnasari, Titin; Purmafitriah, En; Sasvania, Anisa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Turmeric (Curcuma longa L.) leaves, rich in bioactive compounds like tannins, terpenoids, and essential oils, have potential as a mosquito repellent for preventing vector-borne diseases such as dengue, filariasis, and malaria. This study aimed to evaluate the physical stability of repellent lotion formulations containing ethanol extract of turmeric leaves. The research was experimental in nature. Two formulations were prepared using extract concentrations of 10% (F1) and 20% (F2). The turmeric leaves were extracted using the maceration method with 96% ethanol, yielding 4.069%. The physical stability of the repellent lotion was tested using the freeze-thaw method over 12 days, evaluating organoleptic properties, homogeneity, pH, adhesion, and spreadability. Organoleptic testing showed color differences between the formulas. After stability testing, the consistency of the lotions became slightly thinner. Both formulations exhibited good homogeneity. The pH values were within the safe range for skin application. Changes in adhesion and spreadability were influenced by the testing process. In conclusion, the repellent lotion formulations containing turmeric leaf ethanol extract demonstrated good physical stability and met required quality standards.